Complex rehabilitation of erosive tooth wear with digital workflows - Péter Tajti; Gábor Gerber; Péter Hermann; Péter Schmidt (Hungarian Dental Association, 2023)
Introduction: Erosive tooth wear, caused by a combination of exogenous and endogenous factors, affects both the appearance and function of the entire dentition. Early diagnosis and treatment are crucial as the condition affects 30-45% of the population and can result in the destruction of teeth, necessitating complex prosthetic rehabilitation. Case report: Our 39-year-old patient visited the Department of Prosthodontics at Semmelweis University to have her substantially worn teeth restored, which resulted in significant psychosocial deterioration. The pre-prosthetic treatment plan included patient education, motivation, professional oral hygiene treatment, and initial Michigan splint therapy to acclimate the neuromuscular system to the increased occlusal vertical dimension. Michigan splint was fabricated chairside by building up a deep-drawn splint with self-curing acrylic resin. After three months of splint therapy, the process of creating the definitive restoration began. A gothic-arch device was used to determine the vertical and horizontal relationship of the jawbones. A digital face bow was used to establish the relationship between the upper jaw and the rotational axis as well as the individual angle values. Then, both jawbones were scanned with an intraoral scanner. A digital smile design was created and used for the design of the digital wax-up, which was then 3D printed to create a model. The patient tried on the mock-up diagnostic pattern made of self-curing acrylic. The height and appearance of the mock-up were satisfactory; therefore, tooth preparation could begin. After the preparation of the teeth digital impressions were taken. A newly created mock-up that fits the prepared teeth held the bite height while the jaw relation was scanned. To ensure that the final restoration was an exact copy of the accepted mock-up, the "copy-paste dentistry" concept was used. Long-term temporary restorations were made of polymethyl methacrylate and were worn for one month. After the temporary phase, restorations were milled from zirconia and luted with self-adhesive resin cement. Summary: Erosive tooth wear occurs more and more frequently these days, which can not only affect function and aesthetics but can also lead to psychosocial deterioration. During complex prosthetic rehabilitation, gnathological aspects must be taken into account. Digital technologies could help create more predictable outcomes, increasing patient satisfaction.